Why is allegory the basis of Indian style (sabk-e hendi)? - Morteza Ghasemi; Hossein Hasanrezaei; Fatemeh Hakima (مطالعات زبانی و بلاغی)
Most of the books and articles written about the Indian style (the poetry of the Safavid era) have often mentioned allegory as the most important feature of the Indian style. In this relation, Mohammad Siāsi has published a book titled Isfahāni style and Allegory in the Poetry of Sāeb and the poets of the Safavid era. As such, the use of allegory in Indian style poetry is not a new thing, and it has been frequently dealt with until today. The important matter is what the purpose and function of allegory is and why it is the basis of Indian style? This article tries to answer the questions focusing on Asrār al-balāḡa (The secrets of eloquence) of Abd-ul-Qāher Jorjānī, which has the most complete and accurate explanations about allegory, - and additional information about the Indian style and its concurrent society in Iran. The research method is descriptive-analytical and based on the detailed analysis of allegory in the poetry of prominent poets of Indian style. The results of the research show that the most important function of allegory is to make the mental and intangible things tangible so as to convince the audience, especially the general audience, and persuade them to accept the claim or concept in question. Therefore, the most important reason for using allegory is persuading the audience, and secondly, the significance of the meaning of stranger in Indian style, which has made the poets pay attention to the smallest matters of life to make an allegory. In addition to these factors, the poetic realism under the influence of the Voqou (a Persian poetic style which favors simplicity in style and language) and its departure from the court and the surrealist world of mysticism and the Sufi lodges has caused the spread of this literary style. Because this way of expression, while beautiful and wondrous, makes the poem realistic and the poet’s claim acceptable. To these reasons, it is necessary to add the poem beauty and freshness, and the audience fascination.